Si duo faciunt idem, non est idem: The Fate of the German and Albanian National Minorities in Yugoslavia at the End of the Second World War - Zoran Janjetović (Токови историје)
The paper examines the behavior of Yugoslavia’s two largest national minorities during the Second World War. It investigates reasons why the new communist authorities after the war did not punish the ethnic Germans and ethnic Albanians equally for their similar collaborationist attitudes.